2022
DOI: 10.1080/02786826.2022.2110448
|View full text |Cite
|
Sign up to set email alerts
|

The organic coating unit, an all-in-one system for reproducible generation of secondary organic matter aerosol

Abstract: Ozone production in the OCU is a function of flowrate and UV light intensity. Figure S1 shows the range of possible ozone concentrations at three different flowrates measured by means of a 205 Dual Beam Ozone Monitor (2B Technologies, USA).Carrier gas was dry, particle-free, synthetic-air (Carbagas ALPHAGAZ 1 quality, Switzerland). Figure S1: OCU ozone production as a function of number of active UV lamps for different flowrates. Error bars represent the 2% precision of the measurement instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Even though the angles between our spectra and the reference are around 36° (Table S4), they may still be considered as similar, given that we compare experiments performed under different conditions (both in terms of SOM production as well as sample collection) and by using different mass spectrometers. In addition, similarity to literature spectra has been confirmed by LC-MS measurements using the automated version of our particle generation system …”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Even though the angles between our spectra and the reference are around 36° (Table S4), they may still be considered as similar, given that we compare experiments performed under different conditions (both in terms of SOM production as well as sample collection) and by using different mass spectrometers. In addition, similarity to literature spectra has been confirmed by LC-MS measurements using the automated version of our particle generation system …”
Section: Resultssupporting
confidence: 58%
“…In addition, similarity to literature spectra has been confirmed by LC-MS measurements using the automated version of our particle generation system. 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keller et al, 2022, showed that the OCU produces SOA, even at high masses, with an atmospherically relevant, realistic chemical composition when compared to conditions in the low µg/m 3 particle mass range (Keller et al, 2022). In the OCU, an organic precursor is oxidized in a small flow chamber by OH and ozone under controlled relative humidity (65%) and temperature conditions (fully described by Keller et al, 2022) (Keller et al, 2022). 155…”
Section: Offline Measurements 145mentioning
confidence: 99%
“…SOA produced from OH-initiated photooxidation of α-pinene is commonly used as an atmospherically representative SOA (Campbell et al, 2019b). High mass concentration SOA (approximately 80 mg/m 3 ) was produced using the Organic Coating Unit (OCU) (Keller et al, 2022) collected on quartz filters for 100 seconds. These very high aerosol concentrations were necessary to minimize the time between 150 particle generation and analysis and therefore reduce the decay of short-lived OP-active aerosol components.…”
Section: Offline Measurements 145mentioning
confidence: 99%